1971
DOI: 10.1017/s0031182000079968
|View full text |Cite
|
Sign up to set email alerts
|

The structure and development of the protozoonHistomonas meleagridisin the male reproductive tract of its intermediate host,Heterakis gallinarum(Nematoda)

Abstract: The ultrastructure and development ofHistomonas meleagridisin the reproductive tract of maleHeterakis gallinarumhas been described. In the testis the protozoon is a relatively large amoeboid organism which lies between the epithelial cells of the testis and the spermatogonia, spermatocytes and spermatids. It is similar in appearance to the invasive stage which is found in the final host and like the invasive stage, it also feeds upon the host cells by phagocytosis. In the vas deferens the protozoon lies betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The most important role of H. gallinarum is its capability of transferring the protozoon Histomonas meleagridis to fowls [9]. A previous report indicated that an outbreak of histomoniasis due to H. meleagridis developed in a chuchar partridge farm in Korea [10].…”
Section: Discussionmentioning
confidence: 99%
“…The most important role of H. gallinarum is its capability of transferring the protozoon Histomonas meleagridis to fowls [9]. A previous report indicated that an outbreak of histomoniasis due to H. meleagridis developed in a chuchar partridge farm in Korea [10].…”
Section: Discussionmentioning
confidence: 99%
“…Heterakis ova harbouring Histomonas are able to survive in the soil for up to 2 years (Levine, 1985) (Fig. Several studies exist which describe the relationship between Histomonas and H. gallinarum in greater detail (Lund and Burtner, 1957;Kendall, 1959;Gibbs, 1962;Lee, 1969a;Ruff et al 1970;Lee, 1971;Lund and Chute, 1973). The protozoa are liberated when the helminth ova are ingested by an appropriate host and hatch, releasing both immature worms and the protozoa.…”
Section: Histomonas Meleagridis and Parahistomonas Wenrichimentioning
confidence: 99%
“…Organic production, however, represents new challenges as to controlling biosecurity and pathogens. During freerange production, poultry flocks are exposed to the caecal worm Heterakis gallinarum, the intermediate host of Histomonas meleagridis (Gibbs, 1962;Lee, 1971;McDougald, 2005). As chickens constitute an optimal host for the caecal worm (Lund & Chute, 1974), this underlines the risk of outbreak of histomonosis in freerange layer flocks.…”
mentioning
confidence: 99%